Making sense of safety: transforming the corporate safety culture - Lanawaang, Yehuda; Zulfiningrum, Rahmawati (Faculty of Communications Science, Dr. Soetomo University, 2025)
Occupational Safety and Health (OSH) not only depend on regulations, but also on effective communication and meaning-making processes to build a consistent safety culture through information dissemination, training, and continuous education. This study analysed the alignment among workers in raising awareness of occupational safety and health at PT Telkom Akses Regional 4 Central Java-DIY between field and non-field workers. This study used the concept of ‘sensemaking’, which is derived from organizational communication emphasizing the role of transformational leadership in instilling safety values, combined with the process of meaning-making through seven dimensions (based on identity construction, retrospective, perceptible environment, social, sustainable, focused on and by extracted cues, driven by feasibility rather than accuracy), enabling workers to internalise risks based on experience and incidents. This research employed a qualitative approach using a phenomenological method, with data collected through semi-structured interviews, observations, and document analysis at PT Telkom Akses. The research findings indicate that the main challenges in safety culture transformation in companies include the gap between formal policies and field practices and the tendency of workers to ignore procedures because they are considered impractical. The integration of participatory strategies sharing experiences, technical improvements to increase motivation and participation, sharing workplace accident experiences, and transformational leadership (peer mentoring, gamification, storytelling) along with measurable indicators (Key Performance Indicators) based on OSH strengthen message cohesion, supported by double-loop learning for preventive incident documentation and critical reflection, resulting in OSH transformation as a collective responsibility through the internalization of safety values as professional identity.